2020
DOI: 10.1016/j.foreco.2020.117880
|View full text |Cite
|
Sign up to set email alerts
|

The calm before the storm: How climate change drives forestry evolutions

Abstract: Highlights-Climate change weakly modifies forestry compared to techno-economic evolutions.-Most adaptations focus on technical operations and ignore organizational changes.-Ecological processes are instrumental and applied at the forest stand scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Concerning primary data analysis, a mix of quantitative and qualitative methods is used. Qualitative data collection is applied by 17% of papers, mainly adopting semi-structured interviews and questionnaires, e.g., [38,71,72]. These approaches dominate when Concerning primary data analysis, a mix of quantitative and qualitative methods is used.…”
Section: Data Collection Methodologiesmentioning
confidence: 99%
“…Concerning primary data analysis, a mix of quantitative and qualitative methods is used. Qualitative data collection is applied by 17% of papers, mainly adopting semi-structured interviews and questionnaires, e.g., [38,71,72]. These approaches dominate when Concerning primary data analysis, a mix of quantitative and qualitative methods is used.…”
Section: Data Collection Methodologiesmentioning
confidence: 99%
“…Climate studies carry much uncertainty, and forest research deals with issues related to individual preferences such as esthetic inclination, management intensity choices, or risk aversion. The ambiguity resulting from this intertwining of uncertainty and individual values can prejudice the scientific arguments of a study, as previously reported for the technical preferences of windstorm adaptation in forest management (Fouqueray et al 2020). Therefore, one way to pursue the best practices in transparent research is to spell out these individual values, so as not to allow scientists' biases to influence their readers.…”
Section: Social Sciences: An Opportunity For Forest Researchers Doing Climate Studiesmentioning
confidence: 96%
“…Publications have reviewed the "science of adaptation," such as the physiological and evolutive impacts of climate change on trees (Aitken et al 2008), or the evolutive processes favoring adaptation (Bussotti et al 2015). Publications in the "science for adaptation" discuss management practices in favor of adaptation (Keenan 2015;Marchi et al 2018) or report their implementation in the field (Nelson et al 2016;Fouqueray et al 2020). Further research on genetics, physiology, ecology, and climate studies is required to improve our knowledge of forest functioning under a changing climate.…”
Section: Introductionmentioning
confidence: 99%
“…Although it makes sense to monitor how carbon-oriented operations directly influence the role of forests as carbon sinks, the neutral, positive, or negative effects of such operations on forest multifunctionality should not be overlooked [8]. Indeed, many forest stakeholders deem the simultaneous provision of different forest ecosystem services (ES) to be critical [9,10], especially the provision of timber and non-timber forest products, but also the esthetic value of managed landscapes for local communities or tourism development and the role of forest soils in water epuration, to name but a few [11].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale of this paper is to investigate how voluntary mitigation projects boost forest management from the perspective of three essential issues, namely the efficiency, sustainability, and multifunctionality of carbon storage. Drawing deductively on a literature review on forest carbon storage [23] and inductively on our experience with forest practitioners [9], we considered that these were the three best factors predicting the success of mitigation projects. The first factor relates to the efficiency of carbon offsetting.…”
Section: Introductionmentioning
confidence: 99%